The Evolution of a Financial Crisis: Collapse of the Asset‐Backed Commercial Paper Market - COVITZ, DANIEL; LIANG, NELLIE; SUAREZ, GUSTAVO A. (Journal of Finance, 2013)
ABSTRACT This paper documents “runs” on asset‐backed commercial paper (ABCP) programs in 2007. We find that one‐third of programs experienced a run within weeks of the onset of the ABCP crisis and that runs, as well as yields and maturities for new issues, were related to program‐level and macro‐financial risks. These findings are consistent with the asymmetric information framework used to explain banking panics, have implications for commercial paper investors’ degree of risk intolerance, and inform empirical predictions of recent papers on dynamic coordination failures.